Synthesis of Eu2+ and Dy3+ doped strontium aluminates and their properties - Rozenberga-Voska, Laura; Grabis, Janis; Zolotarjovs, Aleksejs (Trans Tech Publications Ltd., 2017)
Strontium aluminate phosphors were synthesized by the solution combustion method using citric acid, urea or glycine as reducing agent and europium and dysprosium as dopants. The content of both dopants was in the range of 1-2 mol%. Dependence of phase composition, crystallite size and specific surface area on calcinations temperature, used reducing agents and dopants were determined. Luminescent properties of the calcinated at 1300 °C powders contained SrAl2O4 (90 %) and Sr4Al24O25 (10%) phases with crystallite size of 80 nm were determined.
Financial support to this project was provided by National Research Programme (IMIS2).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; strontium aluminate phosphors; luminescence; solution combustion method; specific surface area; powder XRD